2020
DOI: 10.1039/d0nr03743e
|View full text |Cite
|
Sign up to set email alerts
|

Security use of the chiral photonic film made of helical liquid crystal structures

Abstract: The color change of photonic crystal (PC) has been widely studied due to its beauty and anti-counterfeiting purpose. Here we demonstrated security codes based on chiral PCs that are not...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The developed systems based on oblate CLC droplets are unique and could demonstrate synergetic color and shape responses. Compared to various color changing systems based on CLCs, [ 26–28,32,55–57 ] our systems have several advantages: 1) A new strategy to achieve large selective Bragg reflection in CLC droplets. CLC droplets or shells could show macroscopic color that is visible by naked eyes only when they are large enough on the scale of hundreds of micrometers.…”
Section: Figurementioning
confidence: 99%
“…The developed systems based on oblate CLC droplets are unique and could demonstrate synergetic color and shape responses. Compared to various color changing systems based on CLCs, [ 26–28,32,55–57 ] our systems have several advantages: 1) A new strategy to achieve large selective Bragg reflection in CLC droplets. CLC droplets or shells could show macroscopic color that is visible by naked eyes only when they are large enough on the scale of hundreds of micrometers.…”
Section: Figurementioning
confidence: 99%
“…TheH NF phaseh as an anoscale helical structure induced by saddlesplay deformation of smecticl ayers (Figure 1) and has potential to be applied in patterning tools based on templates for chirala ssembly [20][21][22][23] andv arious chiro-opticala pplications such as chiral sensors [24] and security codes. [25] In this study,p olymorphs of HNFp hases formed by as ingle kind of molecules were investigated.I tw as found that under differentc onditions-illumination with UV light in the bulk state or geometricaln anoconfinement( Figure 2)-either twisted ribbonso rc ylindrical ribbons are grown.F or these studies, photosensitive azobenzene derivatives and nanoporous anodic aluminumo xide (AAO) having various pore diameters D P were used for light-driven orientation and geometrical nanoconfinement, respectively.The structural analysisineach case was performed by SEM and grazing-incidence X-ray diffraction (GIXD) with synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization-dependent liquid crystal (LC) films have been applied in broad fields, including in LC polarizers [1][2][3][4][5], photo-luminescence films [6][7][8], and photonic crystals [9][10][11]. Among these, dye-doped LC films composed of coaligned LC polymer networks and dichroic dyes attract interest among researchers due to their novel optical property and efficient fabrication process [1][2][3][4][5][6][7][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This conventional film could show a difference in brightness depending on the direction of the incident LPL because almost all dichroic dyes have only one absorption axis, except in special cases [20,21]. To overcome this limitation, chiral photonic crystals [11] or materials that use refractive index change [22] have been proposed, but this method requires expensive and complicated fabrication methods. In this study, we suggest the use of a bilayer dichroic dye-doped LC (BDLC) film as an anti-counterfeiting film with enhanced security.…”
Section: Introductionmentioning
confidence: 99%